PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SD NEGERI 157 PEKANBARU - Sujaunah Sujaunah; Hendri Marhadi; Jesi Alexander Alim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract ; This study in the background of its low background by science students learning outcomes. Itis inevidence right from 32 students only 15 students (46,87%) were scored according minimum completeness criteria (KKM) and 17 students (53,21%) whose grades do not correspond KKM 70 while school set from the 1 semester exam results in the fourth grade IV SD Negeri 157 Pekanbaru country. This research is a classroom action reseach (PTK) conducted aims to improve learning outcomes fourth grade science students SD Negeri 157 Pekanbaru country by implementing cooperative learning tipe Think Pair Share (TPS). The research was conducted on 09 March 2015 to 27 March 2015 by two cycles. The subjects were IV grade students of SD Negeri 157 Pekanbaru totaling 32 people. Data collection instruments in this is a sheet teacher and students activity sheets as well as the achievement test. This thesis presents the results of studying magnified acts with an average of 70,63, an increase in the first cycle with the average being 75,00. In the second cycle increased by an average of 87,03. The activities of teacher in the learning process in the first cycle of the first meeting and the second meeting rose 67,50%, and second meeting 70%, 82,50% cycle two first meeting and the second meeting increased to 90%. Result of the data analysis activity of students in the first cycle of the first meeting of 62,50% in the second meeting increased 70%. At the first meeting of the second cycle of 82,50% and in the second meeting increased to 95%. Research results in the fourth grade elementary school 157 Pekanbaru prove that the implementation of cooperative learning model Think Pair Share (TPS) can improve learning outcomes IPA.Key Word ; cooperative learning model Think Pair Share, outcomes IPA